2019
DOI: 10.1088/1748-0221/14/11/c11020
|View full text |Cite
|
Sign up to set email alerts
|

Systematic errors in tokamak magnetic equilibrium reconstruction: a study of EFIT++ at tokamak COMPASS

Abstract: A: Uncertainties and errors in magnetic equilibrium reconstructions are a wide-spread problem in interpreting experimental data measured in the tokamak edge. This study demonstrates errors in EFIT++ reconstructions performed on the COMPASS tokamak by comparing the outer midplane separatrix position to the Velocity Shear Layer (VSL) position. The VSL is detected as the plasma potential peak measured by a reciprocating ball-pen probe. A subsequent statistical analysis of nearly 400 discharges shows a strong syst… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…The analysis was based on the EFIT equilibrium reconstruction and its accuracy. An investigation of COMPASS data previously reported that there is a significant uncertainty in the estimate of separatrix position [25] and an improved EFIT variant was implemented. In our datasets, the difference between the EFIT variants was minimal and it resulted in a minor change in λ q results (<10% on average).…”
Section: Discussionmentioning
confidence: 99%
“…The analysis was based on the EFIT equilibrium reconstruction and its accuracy. An investigation of COMPASS data previously reported that there is a significant uncertainty in the estimate of separatrix position [25] and an improved EFIT variant was implemented. In our datasets, the difference between the EFIT variants was minimal and it resulted in a minor change in λ q results (<10% on average).…”
Section: Discussionmentioning
confidence: 99%
“…Throughout this paper the radial profiles are plotted relatively to the last closed flux surface (LCFS). The exact position of the LCFS on COMPASS is routinely obtained by means of probes [30] or magnetic equilibrium reconstruction. In this paper we use probe measurements to locate the maximum of plasma potential, which improves the precision of the position of the LCFS compared to the one provided by the magnetic equilibrium reconstruction.…”
Section: Ion and Electron Temperature Ratio In The Solmentioning
confidence: 99%
“…Note that only relative changes of p down /p up are relevant since the determination of separatrix location can exhibit a systematic offset [22], which influences the absolute value of p up . This is a known caveat of equilibrium reconstruction codes, which is commonly assessed by an estimation of the separatrix temperature using the 2 point model for the conductionlimited regime.…”
Section: Plasma Coolingmentioning
confidence: 99%